Cultural adaptation and psychometric properties of the online learning climate scale for Chilean university students - Bravo-Sanzana, Mónica; Miranda, Rafael; Terán-Mendoza, Oscar; Mieres-Chacaltana, Manuel; Carabantes, Luis (Frontiers in Psychology, 2024)
Introduction The COVID-19 pandemic has profoundly changed university teaching and learning formats, leading to a significant increase in online learning. Consequently, the crisis has facilitated the potential development of this educational modality. However, researchers need adapted and validated instruments to assess the online learning climate in universities. Aim This study aimed to adapt and psychometrically validate the Online Learning Climate Scale (OLCS) for Chilean university students. Method Quantitative research was conducted with a non-experimental and cross-sectional, design executed in two phases: the first was oriented to the cultural adaptation of the instrument, and the second was focused on analyzing its psychometric properties in a sample of 491 university students. Results A translated and culturally adapted version was obtained, composed of 15 items distributed in a factorial structure composed of four dimensions that showed excellent adjustment to the data [χ2 (84) = 189.628; p < 0.001; CFI = 0.979; TLI = 0.973; RMSEA = 0.051 (IC90% 0.044–0.059); SRMR = 0.028]; internal consistency was estimated through Cronbach’s alpha and ranged between 0.892 and 0.955, and strict invariance between men and women was achieved. Discussion The Online Learning Climate Scale (OLCS) is a valid and reliable measure for measuring the online learning climate within the Chilean higher education context so that it can be used both in research and in monitoring management programs in educational environments.